Peripherally Inserted Central Catheter Dwell Time as a Risk Factor of Central Line-Associated Bloodstream Infection in Neonates - Dian Ekaputri; Made Sukmawati; I Gusti Lanang Sidiartha; Gusti Ayu Putu Nilawati; I Made Gde Dwi Lingga Utama; I Wayan Gustawan (Mashhad University of Medical Sciences, 2022)
Background: According to the Centres for Disease Control and Prevention, central line-associated bloodstream infection (CLABSI) is a laboratory-confirmed bloodstream infection not related to an infection at another site that develops within 48 h of central line placement. Central line-associated bloodstream infection in the Neonatal Intensive Care Unit contributes to increased morbidity and hospital mortality. This study aimed to prove the relationship between peripherally inserted central catheter dwell time and the incidence of CLABSI among neonates at our tertiary center hospital in Bali, Indonesia. Methods: This study was conducted based on a prospective cohort study design. The subjects were neonates admitted in levels 2 and 3 of the neonatology wards of Sanglah Hospital, Bali, Indonesia, between November 2018 to December 2020. The cases were followed during the insertion of a central catheter. Statistical analysis was performed using the Chi-square test and logistic regression with a p-value of < 0.05. Results: Subjects were recruited consecutively and fulfilled the research criteria as many as 114 people. A total of 63 subjects were excluded, and none of the cases was lost for follow-up. The incidence rate of CLABSI was obtained at 19.2‰ among the 114 subjects. The patients with a catheter dwell time of ˃ 14 days, compared to those with a catheter dwell time of ≤ 14 days, had a 2.9-fold risk of experiencing CLABSI (95% confidence interval: 1.191-7.497, P=0.02). No other risk factors were found for CLABSI development. Conclusion: The results of this study demonstrated that the risk of CLABSI in subjects with a catheter dwell time of ˃ 14 days was 2.9. Therefore, the implementation of the CLABSI bundle is necessary to decrease CLABSI incidence in neonates.